Corporate Social Responsibility Financial Sector in Colombia, History, Evolution and Transformation - Liseth Patricia Ortega Salgado; Orlando Carmelo Castellanos Polo (MultiTech Publisher, 2020)
The purpose of this research is to understand and learn about Corporate Social Responsibility in the Financial Sector in Colombia in terms of the different issues that refer to it as the importance in the transformation and management of financial resources for the good of its interest groups and society. In general, we will see its history, evolution and transformation until today